Development of the Tourism Sphere as a Factor of the Regionallabour Market Regulation - Evgeniy Fedorovich Cheberko; Alexander Markovich Malinin; Darya Andreevna Andreeva (Управленческое консультирование)
The article is dedicated to the prospects of development of tourism sphere as one of factors of regulation of a state and conditions of regional labour markets. The clause broaches a point of connection perspective and a role of the tourism sphere and a state of regional labour market in processes of ensuring sustainable development of the region, that in long terms creates prerequisites to increase in level of economic security of the region, decrease in social tension and realization of opportunities of purposeful regulation of human recourses use in the region.